Buccal cobble stoning – a signpost to diagnosis. (24th May 2012) - McAlonan, C; Goodyear, H
Abstract : Aims: Crohn's Disease is an inflammatory process affecting the entire alimentary canal, most typically the terminal ileum and has a variety of dermatological manifestations. We report a case which presented with genital and buccal mucosal lesions. Methods: Case report and review of the literature Results: A nine year old girl had a six month history of pain after defecation and a month's history of a labial abscess. There was no improvement in symptoms with flucloxacillin, penicillin v and metronidazole. Admission was therefore arranged for intravenous therapy. Her weight had decreased by 1.1 kg over a 2 month period. Inflammatory markers on admission showed an ESR of 60 and a CRP of 5 and her iron levels were low (<5 umol/L). Blood cultures were negative. Labial swabs grew mixed skin and coliform organisms only. On review, her buccal mucosa was noted to show a cobblestone appearance and anal skin tags were present. Referral was made to a tertiary gastroenterology centre who confirmed the working diagnosis of Crohn's Disease. The labial lesion and her anal skin tags improved, as did the other symptoms, on treatment with infliximab and azathioprine. Conclusion: Crohn's Disease is a multisystemic inflammatory granulomatous disease which can present in many different ways. Extra intestinal signs often precede typical intestinal symptoms. Crohn's Disease should be included in the differential diagnosis of labial lesions1 . Although oral involvement is a recognised presenting feature, lesions are usually painful and involve local swelling2 . A discrete cobblestone appearance of the buccal mucosa is, however, an accepted but rare feature of Crohn's Disease2 . It is therefore imperative that a detailed, systemic examination is undertaken as useful signposts to diagnosis can be easily missed.